Comparison of Endoscopic Techniques in the Management of Type I Gastric Neuroendocrine Neoplasia: A Systematic Review - Francesco Panzuto; Ludovica Magi; Gianluca Esposito; Maria Rinzivillo; Bruno Annibale (Gastroenterology Research and Practice)
Background. Endoscopic resection is considered the treatment of choice for type I gastric neuroendocrine neoplasia (gNEN) given its indolent behaviour; however, the favoured endoscopic technique to remove these tumours is not well established. Aims. This systematic review is aimed at investigating the best endoscopic management for type I gNEN. Methods. PubMed Central/Medline and Scopus were systematically searched for records up to August 31, 2020. Results. After screening the 675 retrieved records, 6 studies were selected for the final analysis. The main endoscopic resection techniques described were endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD). Overall, 112 gNENs were removed by EMR and 77 by ESD. Both techniques showed similar results for complete and en bloc resection (97.4% and 98.7%; 92.3% and 96.3% with ESD and EMR, respectively). ESD was associated with a higher rate of complications than EMR (11.7% vs. 5.4%), but this difference was not statistically significant (p=0.17). The rates of recurrence during follow-up were 18.2% and 11.5% for EMR and ESD, respectively. Conclusions. To date, there are no sufficient data showing superiority of a given endoscopic technique over others. Both ESD and EMR seem to be effective in the management of type I gNEN, with a relatively low rate of recurrence.